Professional master program: Preparing the nurse of the future - Maria Itayra Padilha; Isabel Alves Maliska; Roberta Costa; Silvana Alves Benedet; Francine Lima Gelbcke; Jane Cristina Anders (Associação Brasileira de Enfermagem, 2020)
ABSTRACT Objective: Analyze the results of knowledge production from a graduate program for master's degree in nursing. Method: This is a qualitative retrospective documentary study. Data were collected from the university library repository and the program website. In total, 83 dissertations were found, analyzed and arranged into five groups: worker's health, care management, systematization of nursing care, health education, and nursing care. Results: The results indicate good practices such as manuals, guides, protocols, software, and products for systematization of care. They indicate concern about changing the reality with care practices and interventions, health education and continuing education. Final considerations: This study showed student commitment to the fields of practice when choosing the project theme. Students presented an intention to improve care, management, education and research, in the various dimensions of the profession.